Anthropomorphism, perceived learning for creation, and growth creative mindset as predictors of acceptance toward artificial intelligence creativity - Jang, Yei Beech (Social Behavior and Personality, 2023)
Despite the steady increase in art creations generated by artificial intelligence (AI), few empirical studies have examined public acceptance toward AI creativity and the factors influencing this acceptance. This study investigated the relationships among AI anthropomorphism, perceived AI learning for creation, creative mindsets, and acceptance toward AI creativity. I conducted an online survey comprising 505 participants. The results showed that AI anthropomorphism, perceived AI learning for creation, and growth creative mindset were positive predictors of acceptance toward AI creativity. Those with higher levels of AI anthropomorphism, perceived AI learning for creation, and a growth creative mindset were more likely to have stronger acceptance toward AI creativity. The findings of this study shed light on the mechanism of acceptance of AI creativity and provide an opportunity to understand perceptions of human creativity.
Keywords: anthropomorphism; artificial intelligence creativity; artificial intelligence-generated art; growth creative mindset; perceived learning for creation